An Analysis on Network Tourism Development in the Valley of Kashmir: Some Significance: Exploring Adventure Tourism and Regional Development in the Valley of Kashmir (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Kashmir is A definitive Adventure Truth be told, experience tourism in Kashmir is one of the significant draws for the vacationers. The interminable extent of experience tourism in Kashmir is to a great extent a direct result of its various geology and atmosphere. Kashmir offers perfect conditions and incredible breadth for undertaking a scope of experience sports exercises. Kashmir offers the vacationers to browse a plenty of courageous games of trekking, hiking, mountain biking, stream boating, horse polo, golf, para-skimming, angling, skiing, chasing, exploring, kayaking, bicycling, kayak trips, snow skiing, crosscountry skiing, heli-skiing, ski-mountaineering, water skiing, outdoors, shake ascending, climbing, snowboarding and trans-Himalayan jeep safaris. Kashmir is set apart by four seasons and all seasons are passable to take up any experience movement in Jammu and Kashmir. The present investigation will discover the significance of network tourism and provincial development in the Valley of Kashmir.Finally a few proposals will be given in order to upgrade network tourism development in Kashmir Valley.